2004
DOI: 10.1001/archpsyc.61.6.577
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Effectiveness Trial of Interpersonal Psychotherapy forDepressed Adolescents

Abstract: Interpersonal psychotherapy delivered in school-based health clinics is an effective therapy for adolescent depression. This effort is a significant step toward closing the gap between treatment conducted in the laboratory and community clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
361
7
10

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 501 publications
(403 citation statements)
references
References 41 publications
25
361
7
10
Order By: Relevance
“…17 There is a general idea that IPT is especially beneficial for adolescents with high levels of interpersonal conflict with parents, high levels of depressive symptoms, and comorbid anxiety. 23 Family-focused interventions also have the advantage of approaching critical issues of the child's context, emerging as a promising strategy in recent years, especially in young children. 5,24 On the path to define the best treatment option for depression, the Improving the Mood with Psychoanalytic and Cognitive Therapies (IMPACT) trial is an ongoing study that is planned to recruit 540 individuals to compare effectiveness and define superiority in reducing relapse among three approaches, combined with the use of fluoxetine as needed: CBT, short term psychoanalytic therapy, and specialist clinical care.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…17 There is a general idea that IPT is especially beneficial for adolescents with high levels of interpersonal conflict with parents, high levels of depressive symptoms, and comorbid anxiety. 23 Family-focused interventions also have the advantage of approaching critical issues of the child's context, emerging as a promising strategy in recent years, especially in young children. 5,24 On the path to define the best treatment option for depression, the Improving the Mood with Psychoanalytic and Cognitive Therapies (IMPACT) trial is an ongoing study that is planned to recruit 540 individuals to compare effectiveness and define superiority in reducing relapse among three approaches, combined with the use of fluoxetine as needed: CBT, short term psychoanalytic therapy, and specialist clinical care.…”
Section: Treatmentmentioning
confidence: 99%
“…Specific data for fluoxetine suggest a NNT = 5, which is possibly associated with a greater half-life of the drug (smaller effect in cases of poor adherence) and a better design of the studies evaluating this drug. 23 An analysis of the 10 studies cited in the meta-analysis for which results grouped according to age were available found that the response to antidepressant treatment was significant for adolescents (62 vs. 49%), but did not reach statistical significance among children (65 vs. 58%) -possibly due to the high placebo response in this age group. In this meta-analysis, the only antidepressant that demonstrated efficacy in both children and adolescents was fluoxetine.…”
Section: Treatmentmentioning
confidence: 99%
“…The Children's Global Assessment Scale (CGAS) (Schaffer et al 1983) is a modification of the Global Assessment Scale (GAS) for adults (Endicott et al, 1976). It is commonly used for rating functioning in children, and was found to be sensitive to treatment effects in adolescents with depression (Mufson et al 2004). The descriptors of the CGAS scores, however, are not all relevant to PDD and cannot be easily applied to children with these disorders who typically follow abnormal developmental trajectories and present with severe impairments in specific areas of functioning.…”
Section: Introductionmentioning
confidence: 99%
“…These treatments include attachment based family therapy (70), interpersonal psychotherapy (71), acceptance commitment therapy (72), thinking about reward in young people (16), game-based digital interventions (73) and Internet and computer-based therapy (74). However, based on the findings reviewed in this paper we promote the development of neuro-scientifically informed, contextually aware and ecologically sustainable ways to treat adolescent depression in a manner that simultaneously empowers, informs and prepares the young generation for a future with rapidly changing living conditions.…”
Section: Implications For Novel Treatment Strategiesmentioning
confidence: 99%